Protozoan indicators and extracellular polymeric substances alterations in an intermittently aerated membrane bioreactor treating mature landfill leachate. Issue 1 (2nd January 2017) - Remmas, Nikolaos; Melidis, Paraschos; Paschos, Georgios; Statiris, Evangelos; Ntougias, Spyridon
ABSTRACT: A membrane bioreactor was operated under intermittent aeration and various organic loading rates (OLR: 0.070, 0.159 and 0.291 g COD L −1 d −1 ) to remove carbon and nitrogen from mature landfill leachate, where external carbon source (glycerol) addition resulted in effective nitrate removal. A relative increase in soluble microbial product (SMP) over extracellular polymeric substances (EPS) was observed at the highest OLR and glycerol addition, whereas no membrane biofouling occurred. SMP (proteins and carbohydrates) and carbohydrate EPS correlated positively and negatively, respectively, with suspended solids and transmembrane pressure (TMP). Moreover, proteinous SMP significantly correlated with carbon and nitrogen load. Principal component analysis also revealed the influence of leachate organic and nitrogen content on biomass production, TMP and sessile ciliate densities. Although filamentous index (FI) was sustained at high levels (3–4), with Haliscomenobacter hydrossis being the main filamentous bacterium identified, no bulking phenomena occurred. High glycerol addition resulted in a rapid increase in sessile ciliate population. Increased Epistylis and Vorticella microstoma population was detected by microscopic examination during high glycerol addition, while a remarkable Rhogostoma population (supergroup Rhizaria) was identified by molecular techniques. The contribution of Rhizaria in nitrogen processes may lead to the dominance of Rhogostoma during landfill leachate treatment.